Temperature gradients in targets with high-intensity implantation and their influence on the characteristics of ion-modified layers; Gas Discharge Plasmas and Their Applications (GDP 2019) - Ryabchikov A. I. Aleksandr Ilyich; Lopatin I. V.; Ananin P. S. Petr Semenovich; Bleicher G. A. Galina Alekseevna; Ivanova A. I. Anna Ivanovna; Koval T. V. Tamara Vasilievna; Modebadze G. S. Georgy Slavovich; Sivin D. O. Denis Olegovich (2019, 2019)
Заглавие с титульного экрана